Qr-Code Flashcards Assisted by the Synectic Model for Students' Writing Skills - Lestari, Fina Wiji; Purwati, Panca Dewi (Universitas Pendidikan Ganesha, 2025)
Students have difficulty writing conjunctive narrative texts due to lack of understanding, limited teaching materials, and the unavailability of interesting learning media. Learning that only relies on textbooks also makes it difficult for students to express ideas, so that writing becomes unstructured, boring, and does not achieve learning completeness. This research aims to create the effectiveness of QR-Code Flashcard media supported by the synectic model. The method used is development research (Research and Development) with the ADDIE model. The experts who were the subject of the research were material experts and media experts. Small group trials of 9 students. The sampling technique used was purposive. The large group trial amounted to 26 people. Data collection methods using test and non-test techniques. The test technique was carried out by pre-test and post-test, while the non-test technique by conducting interviews, questionnaires, and documentation. The technique used to analyze the data is descriptive analysis of qualitative, quantitative, and inferential statistics. The results showed that there was a significant difference in Indonesian learning outcomes in writing narrative texts with conjunctions before and after using Qr-code flashcard media. It is concluded that the use of QR-code flashcard media with a synectic model to improve the skill of writing conjoined narrative text in grade IV elementary school students.